Komunikasi Organisasi Pimpinan Daerah Muhammadiyah (PDM) Kabupaten Bogor Dalam Meningkatkan Kecerdasan Masyarakat di Bidang Pendidikan Periode 2015/2020 - Teddy Khumaedi (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2025)
Communication events that occur in an organization can be studied, such as whether subordinates carry out the leader's instructions correctly or not, or how they convey complaints to the leader, through communication. This information can be used to determine whether the organizational goals that have been set can be achieved in accordance with the expected results. Establishing a good relationship between the chairman and members of each organization is very important, considering that humans are a very important component in the organization.Starting from political and community groups, Indonesia witnessed the growth of several organizations. Muhammadiyah is one of the largest Islamic social organizations in the country. The name Muhammadiyah is no longer foreign to Indonesian culture as a whole. The Indonesian nation has benefited greatly from the work of Islamic organizations operating in the fields of religion, society and education. Before the Republic of Indonesia proclaimed independence on November 18 1912 in Yogyakarta, K.H. Ahmad Dahlan founded Muhammadiyah.Research methodology using interviews, research and documentation. Interviews conducted by researchers for 5 days were carried out from 15 June 2023 to 19 June 2023 with several questions that had been prepared to obtain information from informants regarding the Communication of the Muhammadiyah Regional Leadership Organization (PDM) Bogor Regency for the 2015/2020 Period in Increasing Community Intelligence.